The Effect of Stock Trading Volume, Earning Volatility and Interest Rate on Stock Price Volatility in Companies Listed on IDX MES BUMN 17 for the 2021–2023 Period - Putri, Nurul Syifa; Juniwati, Endang Jatma (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
This study aims to analyze the effect of trading volume, earning volatility, and interest rates on stock price volatility in companies listed in the IDX MES BUMN 17 index during the 2021–2023 period. Stock price volatility serves as the dependent variable, reflecting price fluctuations due to market dynamics. The independent variables consist of trading volume (stock activity level), earning volatility (profit stability), and interest rates (capital cost indicator). Panel data analysis was applied to 9 selected companies that met the criteria. The study uses secondary data sourced from company financial statements and the official website of the Badan Pusat Statistik (BPS). The results show that partially, trading volume significantly affects stock price volatility, while earning volatility and interest rates do not. However, simultaneously, all three variables influence stock price volatility, indicating that stock fluctuations in BUMN companies are shaped by a combination of market behavior, company performance, and macroeconomic factors.